Analisa Sistem Jaringan Komputer Client Server pada PT. XYZ - Ken Leffi Bachtiar Alfan; Asrul Sani (Jurnal Kendali Teknik dan Sains, 2024)
In an increasingly interconnected world, computer networks play a crucial role in business operations. This research focuses on the analysis of the client-server network system at PT. XYZ, which shares a building with several other companies. The objective is to evaluate the current network infrastructure, identify potential issues, and propose improvements to enhance performance and security. A qualitative approach was employed, utilizing case study methods, interviews, and observations to gather in-depth data on the network's configuration, IP address management, and security measures. The findings indicate that while the existing network functions adequately, there are significant risks associated with user access rights and the need for regular maintenance. The implications of this study suggest that implementing stricter security policies and upgrading bandwidth could mitigate risks and improve overall network reliability, thereby supporting business productivity.